2012
DOI: 10.1021/jf3027759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Time on Polyphenolic Content and Antioxidant Activity in the Pressurized Hot Water Extraction of Deodorized Thyme (Thymus vulgaris)

Abstract: The effects of temperature (50-200 °C) and contact time (5-30 min) on the pressurized hot water extraction of deodorized thyme were explored for antioxidant activity, polyphenol profiles, and total antioxidants. Six not previously reported polyphenolic compounds were identified in thyme. An inverse correlation was found between the antioxidant activity and total antioxidants with the amount and diversity of polyphenols. The highest total extract yield and antioxidant activity were obtained at 200 °C, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
95
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 52 publications
12
95
2
Order By: Relevance
“…According to Fecka and Turek (2008), in hot water and methanol extracts of T. serpyllum and T. vulgaris, the extraction time did not significantly affect polyphenols content. Additionally, the exposure time had no statistically significant influence on polyphenols extraction from wild sage and thyme (Vergara-Salinas et al, 2012;Dent et al, 2013). Moreover, both high temperature and long exposure time can reduce the extraction yield, because of temperature sensitivity and enzymatic degradation and oxidation of polyphenols, as well as polymerization among insoluble constituents (Vergara-Salinas et al, 2012).…”
Section: Heat-assisted Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Fecka and Turek (2008), in hot water and methanol extracts of T. serpyllum and T. vulgaris, the extraction time did not significantly affect polyphenols content. Additionally, the exposure time had no statistically significant influence on polyphenols extraction from wild sage and thyme (Vergara-Salinas et al, 2012;Dent et al, 2013). Moreover, both high temperature and long exposure time can reduce the extraction yield, because of temperature sensitivity and enzymatic degradation and oxidation of polyphenols, as well as polymerization among insoluble constituents (Vergara-Salinas et al, 2012).…”
Section: Heat-assisted Extractionmentioning
confidence: 99%
“…Additionally, the exposure time had no statistically significant influence on polyphenols extraction from wild sage and thyme (Vergara-Salinas et al, 2012;Dent et al, 2013). Moreover, both high temperature and long exposure time can reduce the extraction yield, because of temperature sensitivity and enzymatic degradation and oxidation of polyphenols, as well as polymerization among insoluble constituents (Vergara-Salinas et al, 2012). The main advantages of heat-assisted extraction include (1) the enhancement of polyphenols solubility and mass transfer caused by high temperature, (2) faster kinetics, (3) the efficient extraction and higher polyphenols yield, and (4) simple apparatus and method.…”
Section: Heat-assisted Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porcine (Sus scrofa) brains were obtained from official slaughtered animals, dissected, and homogenised with a Polytron in ice-cold Tris-HCl buffer (20 mM, pH 7.4), to produce a 1 : 2 (w/v) brain tissue homogenate which was centrifuged at 3000g for 10 min. An aliquot (0.1 mL) of the supernatant was incubated with the different solution concentrations (0.2 mL) in the presence of FeSO 4 (10 mM; 0.1 mL) and ascorbic acid (0.1 mM; 0.1 mL) at 37 C for 1 h. The reaction was stopped by the addition of trichloroacetic acid (28% w/v, 0.5 mL), followed by thiobarbituric acid (TBA, 2%, w/v, 0.38 mL), and the mixture was then heated at 80 C for 20 min. Aer centrifugation at 3000g for 10 min to remove the precipitated protein, the colour intensity of the malondialdehyde (MDA)-TBA complex in the supernatant was measured by its absorbance at 532 nm.…”
Section: 7mentioning
confidence: 99%
“…Vergara-Salinas et al 37 reported that for extracting phenolics from thyme with water, 100 C and 5 min are appropriate operating conditions, whereas antioxidantactive non-phenolic compounds were favored at higher temperatures and exposure times. Another recent study, conducted by Martínez-Las Heras et al, 38 concluded that the drying method (including shade-and freeze-drying) and preparation procedures have a great inuence on the stability and extractability of bioactive compounds from persimmon leaves.…”
mentioning
confidence: 99%